PKM Pelatihan Desain Kemasan kepada Karang Taruna Desa Buncitan Sedati Sidoarjo - Riyanto, Darwin Yuwono; Erstiawan, Martinus Sony; Martono, Siswo (Cattleya Darmaya Fortuna, 2025)
The increase in selling value and profit for business actors starts with the attractiveness of packaging, logos, and labels. Many MSMEs do not prioritize packaging, labels, and logos on their products, which can influence the appeal to potential customers and loyal consumers. MSMEs often use third-party services for designing packaging, logos, and labels due to limited skills, time, and self-managed operations. The local youth organizations are involved in designing packaging, logos, and labels because they understand local needs, possess creative and innovative ideas, and incorporate these ideas into packaging designs. Their strong sense of ownership toward the product helps drive promotion efforts. The purpose of this activity is to train the youth organizations to create packaging, logos, and labels using digital technology. The method used involves training and mentoring the youth organizations to create packaging, logos, and labels using the Canva application. The results of this training encourage the youth organizations to develop skills in packaging, logo, and label design and to produce competitive local packaging designs.